Colour effect on physiology in a stimulating environment - Ab Jalil, Nurlelawati; Yunus, R.; Sheikh Said, Normahdiah; Mohamed Iqbal, Mimi Iznita (Universiti Putra Malaysia Press, 2016)
Colour is an environmental stimulus that exerts an influence on human beings in a multitude of ways. The effect of colours has been abundantly and unequivocally demonstrated in previous research on the integration of multimodal approaches such as the psychological, performance and non-performance and preferences assessments. Nevertheless, little research has been conducted locally on the integration of physiological assessment and consideration of subjects' living ecology. This is particularly true in the fild of design. The objective of this paper is to propose an optimal colour for the hostel environment of female university students based on their heart-rate response. Four determined colours, namely strong red, bluish-green, pink and white, were painted in their rooms and divided according to exposures. In the experiment, a test and re-test method of assignment was conducted. The results show that subjects in the strong-red environment were stimulated after a short exposure, while subjects in the bluish-green environment were stimulated after long and sustained periods of exposure. In summary, the significance of a coloured environment is discussed with suggestions for a short, longer and sustainable period of exposure from a physiological perspective, aim of which being engagement.